Banana peel: an effective biosorbent for aflatoxins. Issue 5 (3rd May 2016) - Shar, Zahid Hussain; Fletcher, Mary T.; Sumbal, Gul Amer; Sherazi, Syed Tufail Hussain; Giles, Cindy; Bhanger, Muhammad Iqbal; Nizamani, Shafi Muhammad
ABSTRACT: This work reports the application of banana peel as a novel bioadsorbent for in vitro removal of five mycotoxins (aflatoxins (AFB1, AFB2, AFG1, AFG2) and ochratoxin A). The effect of operational parameters including initial pH, adsorbent dose, contact time and temperature were studied in batch adsorption experiments. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and point of zero charge (pHpzc ) analysis were used to characterise the adsorbent material. Aflatoxins' adsorption equilibrium was achieved in 15 min, with highest adsorption at alkaline pH (6–8), while ochratoxin has not shown any significant adsorption due to surface charge repulsion. The experimental equilibrium data were tested by Langmuir, Freundlich and Hill isotherms. The Langmuir isotherm was found to be the best fitted model for aflatoxins, and the maximum monolayer coverage ( Q 0 ) was determined to be 8.4, 9.5, 0.4 and 1.1 ng mg −1 for AFB1, AFB2, AFG1 and AFG2 respectively. Thermodynamic parameters including changes in free energy (Δ G ), enthalpy (Δ H ) and entropy (Δ S ) were determined for the four aflatoxins. Free energy change and enthalpy change demonstrated that the adsorption process was exothermic and spontaneous. Adsorption and desorption study at different pH further demonstrated that the sorption of toxins was strong enough to sustain pH changes that would be experienced in the gastrointestinal tract. This study suggests that biosorption of aflatoxins by dried banana peel may be an effective low-cost decontamination method for incorporation in animal feed diets.